2018
DOI: 10.14569/ijacsa.2018.090711
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Effect of Use Web 2.0 Technology on Saudi Students’ Motivation to Learn in a Blended Learning Environment

Abstract: Abstract-Students' motivation to learn is the goal of the educational process around the world. There is a close link between learning outcomes and students' motivation to learn. Thus, the success of blended learning in Saudi higher education depends on not only using different teaching methods and massive expenditures on technology but also on students' motivation to learn. The main objective of this study is to measure the effect of using the Web 2.0 technology on students' motivation to learn in a blended l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Similarly, in a study investigating the potential of web 2.0 technologies in distance learning, emerging problems and the effectiveness of web 2.0 tools, noticeably positive results of web 2.0 technologies on students' academic achievement were revealed (Gilani, 2012). In a study by Bin-jomman and Al-Khattabi (2018), the effect of using Web 2.0 technologies in education on the motivation of undergraduate students was examined. In the study, it was found…”
Section: Observationmentioning
confidence: 99%
“…Similarly, in a study investigating the potential of web 2.0 technologies in distance learning, emerging problems and the effectiveness of web 2.0 tools, noticeably positive results of web 2.0 technologies on students' academic achievement were revealed (Gilani, 2012). In a study by Bin-jomman and Al-Khattabi (2018), the effect of using Web 2.0 technologies in education on the motivation of undergraduate students was examined. In the study, it was found…”
Section: Observationmentioning
confidence: 99%
“…The ARCS model has been applied and validated in multiple research in various fields [25]- [29]. The ARCS model combined the theories of learning behavior, cognitive, and effective learning in a framework to measure motivation and learning achievement [26].…”
Section: A Arcs Motivational Framework Modelmentioning
confidence: 99%
“…Reference [26] used the ARCS model to measure students' motivation using blended learning for the Science Computer students at one of the universities in Saudi Arabia. They employed the Instructional Materials Motivational Survey (IMMS) questionnaire, which has 36 items that measured the four categories of the ARCS model.…”
Section: B Related Workmentioning
confidence: 99%